Strength training for children and adolescents - Faigenbaum, A. D. (Clinics in Sports Medicine, 2000)
The potential benefits of youth strength training extend beyond an increase in muscular strength and may include favorable changes in selected health- and fitness-related measures. If appropriate training guidelines are followed, regular participation in a youth strength-training program has the potential to increase bone mineral density, improve motor performance skills, enhance sports performance, and better prepare our young athletes for the demands of practice and competition. Despite earlier concerns regarding the safety and efficacy of youth strength training, current public health objectives now aim to increase the number of boys and girls age 6 and older who regularly participate in physical activities that enhance and maintain muscular fitness. Parents, teachers, coaches, and healthcare providers should realize that youth strength training is a specialized method of conditioning that can offer enormous benefit but at the same time can result in serious injury if established guidelines are not followed. With qualified instruction, competent supervision, and an appropriate progression of the volume and intensity of training, children and adolescents cannot only learn advanced strength training exercises but can feel good about their performances, and have fun. Additional clinical trails involving children and adolescents are needed to further explore the acute and chronic effects of strength training on a variety of anatomical, physiological, and psychological parameters.